ETR 300 : Exclusively Golf House LTD / Rosmawati Ismail .... [et al.] - Ismail, Rosmawati; Muhd Fuad, Faizah; Othman, Nazatul Syima; Mohd Fauzi, Nurul Fazlina; Saari, Shamsila Wazee (2001)
Exclusively Golf House is a partnership business which sell golf equipment and accessories such as golf bags, golf shoes, golf ball, iron (wood), sock, cap, apparels, umbrella, glove, wind stopper, golf net, golf stick and golf video lessons. Our business are form by five partners. There are general manager, administration officer, operational officer, marketing officer and financial officer respectively. One of main factor s why we choose this type of business is because the demand for the golf equipment and accessories is rising in the market nowadays. Therefore, there are wide opportunities to everyone especially the golfer to get the golf equipment and accessories easily besides go to the golf club, which is far.